Laminate, sealant film, packaging bag, package, and wet heat treatment package
A polypropylene-based laminate with specific thermal and fusion properties addresses the challenge of sealing surface fusion in mono-material packaging, ensuring low-temperature heat sealability and recyclability during moist heat treatments.
Patent Information
- Application Number
- JP2023102228
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-06-22
AI Technical Summary
Mono-material packaging materials face challenges in achieving high heat resistance in the outer layer and low-temperature heat sealability in the inner layer, leading to issues such as sealing surface fusion during moist heat treatments like retort processing.
A laminate structure comprising a base material layer and a sealant layer with a surface softening temperature between 110°C and 140°C, and a fusion strength of 2.0 N/15mm or less, both made of polypropylene resin, which allows for low-temperature heat sealing and resistance to sealing surface fusion during moist heat treatments.
The laminate enables low-temperature heat sealability and prevents sealing surface fusion even under moist heat treatments, ensuring easy opening and high recyclability of packaging bags.
Smart Images

Figure 2025002209000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, a sealant film, a packaging bag, a package, and a moist heat treated package. [Background technology]
[0002] In recent years, there has been an increasing need for environmentally friendly, sustainable packaging materials, and progress has been made in the development of packaging materials (mono-material packaging materials) that are composed of laminates of layers containing the same material and have good recyclability.
[0003] Mono-material packaging materials have inner and outer layers that contain the same material, and therefore the outer layer has poor heat resistance compared to packaging materials composed of laminates with inner and outer layers made of different resins (multi-material packaging materials). Therefore, mono-material packaging materials require high heat resistance for the outer layer and a low melting point, i.e. low-temperature heat sealability, for the inner layer.
[0004] As an example of such a mono-material packaging material, Patent Document 1 discloses a composite film having two layers, a base layer and a heat seal layer, with the base layer and the heat seal layer being made of a propylene random copolymer and a high-density polyethylene, respectively. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2022 / 234761 Summary of the Invention [Problem to be solved by the invention]
[0006] However, even though the composite film described in Patent Document 1 has heat sealability at low temperatures (less than 155° C.), when a packaging bag obtained using the composite film is subjected to a moist heat treatment such as a retort treatment at a high temperature of, for example, about 120° C., the inner surfaces (sealed surfaces) of the packaging bag have a seal surface fusion property in which the inner surfaces (sealed surfaces) of the packaging bag are fused together. On the other hand, improving the seal surface fusion resistance may make it impossible to achieve low-temperature heat sealability. The present disclosure has been made in consideration of the above circumstances, and aims to provide a laminate, a sealant film, a packaging bag, a packaging body, and a moist heat-treated packaging body that have low-temperature heat sealability and excellent sealing surface fusion resistance even when subjected to moist heat treatment. [Means for solving the problem]
[0007] One aspect of the present disclosure provides a laminate comprising at least a base layer and a sealant layer, wherein the seal surface of the sealant layer has a surface softening temperature of 110°C or higher and 140°C or lower as determined by local thermal analysis, and the sealant layer has a fusion strength of 2.0 N / 15 mm or lower when heat-sealed to the same sealant layer under conditions of 121°C, 0.05 MPa and 30 seconds, and wherein the base layer and the sealant layer contain a polypropylene-based resin. The laminate has low-temperature heat sealability and excellent resistance to sealing surface fusion even after moist heat treatment. Specifically, when the laminate is used to prepare a packaging bag, the laminate can be heat-sealed at a lower temperature when the sealing surfaces of the laminate face each other and are heat-sealed, as compared with the case where the surface softening temperature of the sealing surfaces exceeds 140° C. as determined by local thermal analysis. Furthermore, even when the laminate is used to prepare a packaging bag by heat-sealing the sealing surfaces of the laminate and the packaging bag containing the contents is subjected to moist heat treatment, the laminate can suppress the occurrence of fusion between the sealing surfaces, as compared with the case where the fusion strength exceeds 2.0 N / 15 mm.
[0008] The laminate is preferably subjected to a heating and pressurizing treatment under conditions of 0.33 MPa, 130° C., and 30 minutes, and then the surface softening temperature of the sealing surface determined by local thermal analysis is preferably 140° C. or higher and 150° C. or lower. In this case, the laminate has low-temperature heat sealability and excellent resistance to sealing surface fusion even when subjected to moist heat treatment. Therefore, even when the laminate is used to prepare a packaging bag by heat sealing the sealing surfaces together and the packaging bag containing the contents is subjected to moist heat treatment, the occurrence of fusion between the sealing surfaces can be sufficiently suppressed.
[0009] In the above laminate, when the sealant layer is heat-sealed to the same sealant layer as the above sealant layer under conditions of 0.05 MPa and 30 seconds, it is preferable that T2-T1 is 10.0 N / 15 mm or less, where T1 (N / 15 mm) is the fusion strength when the heat sealing temperature is 121°C and T2 (N / 15 mm) is the fusion strength when the heat sealing temperature is 128°C. In this case, the laminate has resistance to sealing surface adhesion even when subjected to moist heat treatment at 125° C. or higher. Therefore, the laminate can suppress the occurrence of sealing surface adhesion even when the laminate is used to prepare a packaging bag by heat sealing the sealing surfaces together, and the packaging bag containing the contents is subjected to moist heat treatment at 125° C. or higher.
[0010] In the total reflection infrared absorption spectrum of the above seal surface, -1 More than 983cm -1 The peak intensity of the absorption peak appearing in the first region below is P1, 700 cm -1 More than 750cm -1 When the peak intensity of one absorption peak appearing in the second region below is P2, and when two or more absorption peaks are present in the second region, the peak intensity of the absorption peak on the higher wavenumber side of the two absorption peaks with the largest peak intensities in the second region is P3, and the peak intensity of the absorption peak on the lower wavenumber side is P4, it is preferable that the peak intensity ratio P2 / P1 or P3 / P1 is 0.15 or less, or P4 / P3 is 1.5 or less. In this case, the laminate has better resistance to adhesion of the sealed surfaces even after the moist heat treatment, and therefore, even when the laminate is used to prepare a packaging bag by heat sealing the sealed surfaces together and the packaging bag containing the contents is subjected to moist heat treatment, the laminate can effectively prevent adhesion of the sealed surfaces together.
[0011] When the sealant layer is heat sealed to the same sealant layer under conditions of 135° C., 0.05 MPa and 30 seconds, it preferably has a fusion strength of 10.0 N / 15 mm or less. In this case, the laminate has resistance to sealing surface fusion even when subjected to moist heat treatment at 130° C. or higher. Therefore, the laminate can suppress the occurrence of fusion between the sealing surfaces even when the laminate is used to prepare a packaging bag by heat sealing the sealing surfaces together and the packaging bag containing the contents is subjected to moist heat treatment at 130° C. or higher.
[0012] The laminate preferably further includes a gas barrier layer. In this case, the gas barrier property of the laminate is further improved. Therefore, when a packaging bag is produced using the laminate and a package is produced by placing contents in the packaging bag, the laminate can effectively suppress deterioration of the contents due to gases such as oxygen.
[0013] Another aspect of the present disclosure provides a packaging bag obtained by using the above-mentioned laminate and heat-sealing the sealing surfaces together. This packaging bag has low-temperature heat sealability and can suppress fusion between the sealed surfaces even when subjected to moist heat treatment. The packaging bag may be used for purposes requiring heat treatment at 80° C. or higher.
[0014] Yet another aspect of the present disclosure provides a sealant film comprising a polypropylene-based resin, the sealant film having a surface softening temperature of 110°C or higher and 140°C or lower as determined by local thermal analysis of a sealing surface thereof, and having a fusion strength of 2.0 N / 15 mm or lower when the sealant film is heat sealed to the same sealant film under conditions of 121°C, 0.05 MPa, and 30 seconds. Since this sealant film is heat-sealed at a low temperature, when a packaging bag is produced using a laminate formed with a base layer containing a polypropylene resin, the laminate can be heat-sealed at a low temperature by facing the sealing surfaces of the laminate and heat-sealing them together. Furthermore, when a packaging bag is produced using a laminate formed with a base layer containing a polypropylene resin, and the sealing surfaces are heat-sealed together, the occurrence of fusion between the sealing surfaces can be suppressed even when a moist heat treatment is performed.
[0015] Yet another aspect of the present disclosure provides a packaging body comprising a packaging bag and contents contained within the packaging bag, the packaging bag being formed using the above-described laminate, and the sealing surface constituting an inner surface of the packaging bag. According to this package, even when a moist heat treatment is performed, the occurrence of fusion between the sealed surfaces of the packaging bags can be suppressed. Therefore, the package can be easily opened. Furthermore, after the package is opened, the contents can be easily removed and sufficiently discharged. As a result, the packaging bag remaining after the contents are discharged can have high recyclability. Furthermore, according to the above package, since the laminate has low-temperature heat sealability, when the packaging bag is formed, deterioration due to heat of layers in the laminate other than the sealant layer can be suppressed. Therefore, deterioration of the quality of the contents of the package can be suppressed.
[0016] Yet another aspect of the present disclosure provides a moist heat treated package comprising a packaging bag and contents to be accommodated in the packaging bag, the packaging bag being formed using a laminate, the laminate comprising at least a base material layer and a sealant layer, the sealant layer having a sealing surface having a surface softening temperature of 140°C or higher and 150°C or lower as determined by local thermal analysis, the base material layer and the sealant layer comprising a polypropylene-based resin, and the sealing surface constituting the inner surface of the packaging bag. According to this moist heat treated package, the laminate can prevent the sealing surfaces of the packaging bags from fusing together due to the moist heat treatment, so that the sealing surfaces of the moist heat treated packaging bags are prevented from fusing together. Therefore, the moist heat treated package can be easily opened. After the moist heat treated package is opened, the contents can be easily removed and sufficiently discharged. As a result, the packaging bag remaining after the contents are discharged can have high recyclability. Effect of the Invention
[0017] According to the present disclosure, there are provided a laminate, a sealant film, a packaging bag, a package, and a moist heat treated package that have low-temperature heat sealability and excellent sealing surface fusion resistance even when subjected to moist heat treatment. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of one embodiment of a laminate according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic diagram of one embodiment of the packaging body of the present disclosure. [Diagram 3] FIG. 3 is a plan view showing a sealed body used for measuring the fusion strength of a sealant layer. [Figure 4] FIG. 4 is a cross-sectional view that illustrates a schematic diagram of one embodiment of a moist heat treatment package according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, embodiments of the present disclosure will be described. Note that the same components are given the same reference numerals and duplicated explanations will be omitted. Furthermore, the dimensional ratios in the drawings are not limited to the ratios shown in the drawings.
[0020] [Laminate] First, an embodiment of the laminate of the present disclosure will be described with reference to Fig. 1. Fig. 1 is a cross-sectional view that illustrates a schematic diagram of one embodiment of the laminate of the present disclosure. 1, the laminate 100 includes at least a base layer 10 and a sealant layer 30. The surface of the sealant layer 30 opposite to the base layer 10 is a sealing surface 30a. The base layer 10 and the sealant layer 30 contain a polypropylene-based resin. In the sealant layer 30, the surface softening temperature of the sealing surface 30a is 110° C. or higher and 140° C. or lower, as determined by local thermal analysis. Furthermore, the sealant layer 30 has a fusion strength of 2.0 N / 15 mm or less when heat sealed to the same sealant layer as the sealant layer 30 under conditions of 121° C., 0.05 MPa and 30 seconds.
[0021] The laminate 100 may further include an intermediate layer 20 between the base material layer 10 and the sealant layer 30. The laminate 100 may further include a printed layer, if necessary.
[0022] The laminate 100 has low-temperature heat sealability and excellent resistance to sealing surface fusion even after wet heat treatment. Specifically, when the laminate 100 is used to prepare a packaging bag, if the sealing surfaces 30a of the laminate 100 are placed opposite each other and heat sealed, the heat seal can be performed at a lower temperature than when the surface softening temperature of the sealing surfaces 30a measured by local thermal analysis exceeds 140° C. In addition, even when the laminate 100 is used to prepare a packaging bag by heat sealing the sealing surfaces 30a of the laminate 100 and the packaging body containing the contents is subjected to wet heat treatment, the laminate 100 can suppress the occurrence of fusion between the sealing surfaces 30a compared to when the above fusion strength exceeds 2.0 N / 15 mm.
[0023] The laminate 100, the base layer 10, the sealant layer 30, the intermediate layer 20 and the printed layer will be described in detail below.
[0024] (Laminate) The content of the polypropylene-based resin in the laminate 100 is not particularly limited, but is preferably 72% by mass or more. In this case, it is possible to improve the recyclability of the laminate 100. From the viewpoint of further improving the recyclability, the content of the polypropylene-based resin in the laminate 100 is more preferably 92% by mass or more, and even more preferably 95% by mass or more.
[0025] (base material layer) The base layer 10 is a layer that supports the sealant layer 30, and contains a polypropylene-based resin.
[0026] The polypropylene-based resin contained in the base layer 10 is composed of a resin containing propylene as a constituent unit. Examples of polypropylene-based resins include homopolypropylene, propylene copolymers obtained by copolymerizing propylene with ethylene or an α-olefin such as butene, and ethylene-propylene rubber. These can be used alone or in combination of two or more. Examples of the propylene copolymer include a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, and a propylene-ethylene terpolymer. The polypropylene-based resin may be a block polypropylene, which is a mixture of homopolypropylene and ethylene propylene rubber.
[0027] The base layer 10 may be a non-stretched film or a stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film. The base layer 10 may be a laminate including a stretched film and a non-stretched film. The base layer 10 preferably has a biaxially stretched film. In this case, the mechanical strength and dimensional stability of the laminate 100 can be improved.
[0028] The surface of the base layer 10 on the side of the sealant layer 30 may be subjected to various pretreatments such as corona treatment, plasma treatment, ozone treatment, and frame treatment, or may be provided with a coating layer such as an easy-adhesion layer. The base layer 10 may contain a resin other than a polypropylene-based resin. Examples of such a resin include polyolefin-based resins such as polyethylene-based resins. The base layer 10 may contain at least one additive selected from a filler, an antistatic agent, a plasticizer, a lubricant, an antioxidant, and the like, as necessary.
[0029] (Sealant layer) The sealant layer 30 is a layer that imparts heat-sealing sealability to the laminate 100, and contains a polypropylene-based resin. The polypropylene-based resin contains a resin containing propylene as a constituent unit. Examples of the polypropylene-based resin include homopolypropylene, propylene copolymers obtained by copolymerizing propylene with ethylene or an α-olefin such as butene, and ethylene-propylene rubber. These may be used alone or in combination of two or more. Examples of the propylene copolymer include a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, and a propylene-ethylene terpolymer. The polypropylene-based resin may be a block polypropylene, which is a mixture of homopolypropylene and ethylene propylene rubber.
[0030] The sealant layer 30 may be a non-stretched film or a stretched film, but is preferably a non-stretched film from the viewpoints of lowering the heat sealing temperature and improving the sealability by heat sealing.
[0031] The sealant layer 30 may be constructed of a single layer or a laminate of multiple layers.
[0032] The thickness of the sealant layer 30 may be, for example, 20 μm or more, 60 μm or more, or 100 μm or more. The thickness of the sealant layer 30 may be 150 μm or less, 100 μm or less, or 60 μm or less, but is preferably 100 μm or less. When the thickness of the sealant layer 30 is 100 μm or less, the amount of heat required for heat sealing is easily reduced, and damage caused by heat to the base layer 10 and the intermediate layer 20 in the laminate 100 is easily reduced.
[0033] (1) Surface softening temperature of the seal surface (1-1)Surface softening temperature B The surface softening temperature (hereinafter also referred to as "surface softening temperature B") of the sealing surface 30a determined by local thermal analysis is 110°C or higher and 140°C or lower, as described above. When the surface softening temperature B is 110°C or higher, there is an advantage in that the sealing surface has better resistance to fusion even after wet heat treatment, compared to when the surface softening temperature B is lower than 110°C. Furthermore, when the surface softening temperature B is 140°C or lower, heat sealing can be performed at a lower temperature, compared to when the surface softening temperature B is higher than 140°C. The surface softening temperature B may be 115° C. or more, 120° C. or more, or 125° C. or more. The surface softening temperature B may be 138°C or less, 135°C or less, 133°C or less, or 130°C or less.
[0034] For example, when the polypropylene-based resin used for the sealant layer 30 contains homopolypropylene or block polypropylene, the sealant layer 30 has a high surface softening temperature B. On the other hand, when the polypropylene-based resin contains random polypropylene or elastomer, the sealant layer 30 has a low surface softening temperature B. Therefore, by appropriately adjusting the type and blending ratio of the polypropylene-based resin, the surface softening temperature B of the sealant layer 30 can be adjusted to a desired value.
[0035] The surface softening temperature is the temperature at which a material such as a resin exhibits softening behavior. In this embodiment, the surface softening temperature A is measured by performing local thermal analysis (LTA) on the sealing surface 30a of the sealant layer 30 using an atomic force microscope (AFM). Specifically, the surface softening temperature A is calculated as follows. First, the sealant layer 30 is prepared. At this time, the sealant layer 30 itself may be prepared, or a laminate obtained by attaching another film such as the base layer 10 to the sealant layer 30 may be prepared. In order to measure the surface softening temperature A, the sealant layer 30 is heated by applying a voltage to a cantilever having a heater. In local thermal analysis (LTA), after measuring the shape of the surface (sealing surface 30a) of the sealant layer 30, a constant force (contact pressure) is applied to a predetermined location on the surface of the sealant layer 30 with a cantilever, and heating is performed while maintaining the contact pressure constant. The temperature at which a change in the height position (Z displacement) of the cantilever occurs due to a change in the hardness of the sealing surface 30a before and after heating is calculated as the surface softening temperature. The change in the height position of the cantilever refers to a change due to a rise in the vertical position of the cantilever due to thermal expansion of the sealing surface 30a and a fall in the vertical position of the cantilever due to softening of the sealing surface 30a. By converting the voltage applied to the heater of the cantilever when such a change in the height position of the cantilever occurs into the surface softening temperature, the softening temperature can be known locally in the nanoscale region and near the surface.
[0036] In order to convert the voltage applied to the heater of the cantilever into a softening temperature, a calibration curve of the applied voltage and temperature is created. Four types of polymeric materials with melting points differing by 50°C or more are used as the calibration samples. These polymeric materials include materials whose melting points are equal to or higher than the surface softening temperature of the sealant layer 30, and materials whose melting points are equal to or lower than the surface softening temperature. The melting points (melting peak temperatures) of the calibration samples are measured in advance using a differential scanning calorimeter (DSC), and the melting points are taken as the surface softening temperatures of the calibration samples. Local thermal analysis is performed at different measurement positions for each calibration sample, and a calibration curve is created by approximating the average value of the applied voltage at the obtained softening points and the softening temperatures of the calibration samples (melting points measured by DSC) with a cubic function using the least squares method, and this calibration curve is taken as the calibration curve.
[0037] Using this calibration curve of applied voltage and temperature, the temperature corresponding to the applied voltage at the softening point is obtained, and this temperature is taken as the surface softening temperature. In this way, the surface softening temperature is calculated.
[0038] (1-2)Surface softening temperature A In the sealant layer 30, the surface softening temperature (hereinafter also referred to as "surface softening temperature A") determined by local thermal analysis on the seal surface 30a after pressure and heat treatment under conditions of 0.33 MPa, 130°C, and 30 minutes is preferably 140°C or higher and 150°C or lower. By having a surface softening temperature A of 150° C. or less, the laminate 100 can have low-temperature heat sealability. In addition, by having a surface softening temperature A of 140° C. or more, the laminate 100 can have better resistance to sealing surface fusion even when subjected to moist heat treatment. Therefore, even when the laminate 100 is used to produce a packaging bag by heat sealing the sealing surfaces 30a together, and the packaging bag containing the contents is subjected to moist heat treatment, the laminate 100 can sufficiently suppress the occurrence of fusion between the sealing surfaces 30a. The surface softening temperature A may be 143°C or more, 145°C or more, or 146°C or more. The surface softening temperature A may be 149° C. or lower, or 148° C. or lower. The surface softening temperature A can be measured in the same manner as the surface softening temperature B.
[0039] The above-mentioned pressurization and heat treatment is a process for simulating the effect on the sealant layer 30 of heat in a wet heat treatment.
[0040] (2) Fusion strength The sealant layer 30 has a fusion strength T1 of 2.0 N / 15 mm or less when heat-sealed to the same sealant layer as the sealant layer 30 under conditions of 121° C., 0.05 MPa, and 30 seconds. Since the fusion strength T1 is 2.0 N / 15 mm or less, the laminate 100 can suppress fusion between the seal surfaces 30a even when the laminate 100 is used to heat-seal the seal surfaces 30a of the sealant layer 30 to produce a packaging bag, and the packaging bag containing contents is subjected to a moist heat treatment. The fusion strength T1 may be 1.8 N / 15 mm or less, or may be 1.6 N / 15 mm or less. The fusion strength T1 may be 0 N / 15 mm or may be greater than 0 N / 15 mm. The fusion strength may be 0.1 N / 15 mm or more, 0.3 N / 15 mm or more, or 0.5 N / 15 mm or more. The sealant layer that is the same as the sealant layer 30 refers to a sealant layer that is the same in terms of constituent material and thickness as the sealant layer 30 .
[0041] When the sealant layer 30 is heat-sealed to the same sealant layer as the sealant layer 30 under conditions of 128°C, 0.05 MPa, and 30 seconds, the fusion strength is T2 (N / 15 mm), but T2-T1 is not particularly limited, and is preferably 10.0 N / 15 mm or less, more preferably 8 N / 15 mm or less, and particularly preferably 6 N / 15 mm or less. When T2-T1 is 10.0 N / 15 mm or less, the laminate 100 has a seal surface fusion resistance even against a wet heat treatment at 125°C or more. Therefore, the laminate 100 can suppress the occurrence of fusion between the seal surfaces 30a even when the laminate 100 is used to heat-seal a packaging bag to prepare a packaging bag, and the packaging bag containing the contents is subjected to a wet heat treatment at 125°C or more. T2-T1 may be 0 N / 15 mm or may be greater than 0 N / 15 mm. If T2-T1 is greater than 0 N / 15 mm, it may be 0.1 N / 15 mm or greater, 0.5 N / 15 mm or greater, or 1.0 N / 15 mm or greater.
[0042] When sealant layer 30 is heat sealed to the same sealant layer as sealant layer 30 under conditions of 135° C., 0.05 MPa and 30 seconds, sealant layer 30 preferably has a fusion strength T3 of 10.0 N / 15 mm or less. In this case, the laminate 100 has resistance to sealing surface fusion even when subjected to moist heat treatment at 130° C. or higher. Therefore, even when a packaging bag is made by heat sealing the sealing surfaces 30a of the laminate 100 and the packaging bag containing contents is subjected to moist heat treatment at 130° C. or higher, the laminate 100 can suppress the occurrence of fusion between the sealing surfaces 30a. The fusion strength T3 may be 8.0 N / 15 mm or less, or 5.0 N / 15 mm or less. The fusion strength T3 may be 1.0 N / 15 mm or more, or 2.0 N / 15 mm or more.
[0043] The fusion strength is measured by a T-peel test. Hereinafter, a method for measuring the fusion strength will be described with reference to Fig. 3. Fig. 3 is a plan view showing a sealed body used for measuring the fusion strength of a sealant layer. First, two films made of a sealant layer to be used for the measurement are prepared. As shown in FIG. 3, each film is prepared so that the length in the machine direction (MD direction) during film formation is 60 mm, and the length in the direction perpendicular to the MD direction (TD direction) during film formation is 120 mm. Then, the two films are overlapped, and a region 10 mm wide from the edge 600a in the TD direction is heat-sealed by heating at a predetermined heat-sealing temperature (121°C, 128°C, or 135°C) while applying pressure at 0.05 MPa for 30 seconds, to form a heat-sealed portion 610 shown by hatching. In this way, a sealed body 600 is obtained. The heat-sealed portion 610 is a region having a length of 10 mm in the MD direction and a length of 120 mm in the TD direction. Next, a portion 620 indicated by a dashed line in FIG. 3 is cut out from the seal body 600 to obtain a test piece having a width of 15 mm in the TD direction and a length of 60 mm in the MD direction. Finally, a T-peel test is performed using the test piece. The T-peel test is performed in accordance with JIS K 6854-3. The tensile strength at which the heat-sealed portion of the test piece is peeled off is taken as the fusion strength of the heat-sealed portion under the heat-sealing conditions. In this way, the fusion strength is measured.
[0044] (3) Peak intensity ratio in total reflection infrared absorption spectrum When the total reflection infrared absorption spectrum of the seal surface 30a was measured, the sealant layer 30 contained a polypropylene-based resin (e.g., a random polypropylene copolymer) and thus exhibited a peak at 963 cm ―1 More than 983cm ―1 In the first region below, one absorption peak derived from the methyl group of the polypropylene resin appears. In addition, when the polypropylene resin contained in the sealant layer 30 contains a methylene group, ―1 More than 750cm ―1 An absorption peak derived from the methylene group appears in the second region below. When the content of the polyethylene resin in the sealant layer 30 increases or the type of the polypropylene resin becomes, for example, block polypropylene, this absorption peak is split into two absorption peaks due to a change in crystallinity. Here, if the peak intensity of the absorption peak appearing in the first region is P1, if there is one absorption peak appearing in the second region, the peak intensity of that absorption peak is P2, and if two or more absorption peaks appear in the second region, the peak intensity of the absorption peak on the higher wavenumber side of the two largest absorption peaks in the second region is P3 and the peak intensity of the absorption peak on the lower wavenumber side is P4, it is preferable that the peak intensity ratio P2 / P1 is 0.15 or less, P3 / P1 is 0.15 or less, or P4 / P3 is 1.5 or less. In this case, the laminate 100 has better resistance to sealing surface fusion even after a moist heat treatment. Therefore, even when a packaging bag is made by heat sealing the sealing surfaces 30a of the laminate 100 and the packaging bag contains contents, the laminate 100 can effectively prevent the occurrence of fusion between the sealing surfaces 30a.
[0045] P2 / P1 or P3 / P1 is preferably 0.15 or less, more preferably 0.13 or less, in which case, compared to when P2 / P1 or P3 / P1 exceeds 0.15, the occurrence of fusion between the seal surfaces 30a can be more effectively suppressed even when a wet heat treatment is performed at a high temperature. P2 / P1 or P3 / P1 may be 0.04 or more, or may be 0.06 or more.
[0046] It is preferable that P4 / P3 is 1.2 or less. P4 / P3 may be 0.5 or more, or may be 1.0 or more.
[0047] The total reflection infrared absorption spectrum is an infrared absorption spectrum obtained by irradiating the sealing surface 30a of the sealant layer 30 with infrared light through a prism and measuring the light totally reflected at the interface between the sealant layer 30 and the prism. The peak intensity of each absorption peak refers to the difference between the intensity at the maximum point of the absorption peak and the intensity at the baseline in the total reflection infrared absorption spectrum measured as described above.
[0048] When the sealant layer 30 contains a large amount of homopolypropylene, or contains a propylene copolymer in which the propylene copolymer contains a large amount of propylene, the proportion of methyl groups in the sealant layer 30 increases, and the value of P1 tends to become larger. On the other hand, when the sealant layer 30 contains a large amount of a material containing methylene groups and having a low degree of crystallinity, such as polyethylene or random polypropylene containing ethylene as a structural unit, the absorption peak of the second region is less likely to split. In this case, the higher the proportion of ethylene in the polyethylene or propylene copolymer in the sealant layer 30, the larger the value of P2 tends to be. Furthermore, when the sealant layer 30 contains a large amount of a material having a high crystallinity and containing methylene groups, such as block polypropylene, the absorption peak of the second region is likely to split. In this case, the higher the proportion of block polypropylene in the sealant layer 30, the larger the values of P3 and P4, and especially the value of P4. Therefore, by appropriately adjusting the type of polypropylene-based resin and the blending ratio of polyethylene-based resin contained in the sealant layer 30, the peak intensity ratios P1 / P2, P3 / P2, and P3 / P4 can be adjusted to desired values.
[0049] (Middle class) The intermediate layer 20 may be, for example, a gas barrier film. By providing the laminate 100 with a gas barrier film as the intermediate layer 20, when a packaging bag is produced using the laminate 100 and a package is produced by placing contents in the packaging bag, deterioration of the contents due to gases such as oxygen can be effectively suppressed. The gas barrier film includes a gas barrier layer. The gas barrier layer may include a vapor-deposited layer composed of an inorganic compound.
[0050] The inorganic compounds that make up the deposition layer include SiO X and AlO X etc. As a gas barrier layer, for example, SiO X When using a gas barrier layer, the gas barrier layer becomes transparent, so that the contents can be visually confirmed from the outside of the packaging bag. The deposition layer is SiO X and AlO X The inorganic compound such as the above can be formed by vacuum deposition. The thickness of the deposition layer may be, for example, 15 to 30 nm. The gas barrier film only needs to include a gas barrier layer, and may be composed of only a gas barrier layer, or may include a resin film (plastic film), an anchor coat layer, and a gas barrier layer in this order. Here, the gas barrier layer may be provided on either the base layer 10 side or the sealant layer 30 side of the resin film.
[0051] Although the gas barrier layer has gas barrier properties even if it is composed of only a vapor-deposited layer, it is preferable that the gas barrier layer is composed of a composite layer formed by further laminating a coating layer on the vapor-deposited layer.
[0052] When the gas barrier layer is composed of a composite layer, a reaction layer between the deposition layer and the coating layer occurs at the interface between the two layers, or the coating layer fills or reinforces defects or micropores such as pinholes, cracks, and grain boundaries that occur in the deposition layer, forming a dense structure. Therefore, a gas barrier layer composed of a composite layer combining a coating layer and a deposition layer realizes higher gas barrier properties, moisture resistance, and water resistance, and has flexibility that can withstand deformation due to external forces, thereby imparting suitability to the laminate 100 as a packaging material.
[0053] The coating layer can be formed, for example, by a coating method in which a coating agent is applied onto the vapor deposition layer and dried by heating. The coating agent can be based on an aqueous solution or a water / alcohol mixed aqueous solution containing at least one of a water-soluble polymer and one or more alkoxides, their hydrolysates, or tin chloride. The coating agent may further contain a silane monomer. In this case, the adhesion between the coating layer and the vapor deposition layer can be improved.
[0054] The anchor coat layer can be formed by using a curable compound (resin) such as urethane acrylate, etc. The anchor coat layer can be formed by coating a paint in which the curable compound is dissolved in a solvent using a coating method that applies a printing method such as gravure coating or a generally known coating method.
[0055] The resin film may contain a resin. The resin is not particularly limited, but is preferably a polypropylene-based resin. When the resin film contains a polypropylene-based resin, the laminate 100 has a higher recyclability. The resin film may be a non-stretched film or a stretched film, but from the viewpoints of heat resistance and dimensional stability, a stretched film is preferable. The stretched film may be a uniaxially stretched film or a biaxially stretched film. When the stretched film is a biaxially stretched film, the strength and transparency of the laminate 100 are further improved. The thickness of the resin film may be appropriately set depending on the application of the laminate 100, and may be 10 μm or more, or 15 μm or more. The thickness of the resin film may be 40 μm or less, or 25 μm or less. The intermediate layer 20 may be an adhesive layer instead of a gas barrier layer, or may further include an adhesive layer.
[0056] (Printing layer) The laminate 100 may include a printed layer as previously described. The printed layer can be provided on at least one surface of the base layer 10 or on at least one surface of the intermediate layer 20 . The print layer is provided at a position visible from the outside of the laminate 100 for the purposes of displaying information about the contents, identifying the contents, improving concealment, or improving the design of the packaging bag. The printing ink is not particularly limited, and is appropriately selected from known printing inks taking into consideration printability on other layers in the laminate 100, design such as color tone, adhesion, and safety as a food container. The printing method is not particularly limited and may be appropriately selected from known printing methods. Examples of printing methods that may be used include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. Among these, gravure printing is preferably used from the viewpoints of productivity and high definition of the pattern.
[0057] [Sealant film] Next, an embodiment of the sealant film of the present disclosure will be described. The sealant film of the present disclosure is composed of the above-mentioned sealant layer 30. That is, the sealant film contains a polypropylene-based resin, has a sealing surface 30a, and has a surface softening temperature of the sealing surface 30a according to local thermal analysis of 110°C or higher and 140°C or lower, and has a fusion strength of 2.0 N / 15 mm or lower when heat-sealed under conditions of 121°C, 0.05 MPa, and 30 seconds.
[0058] Since this sealant film is heat-sealed at a low temperature, when a packaging bag is produced using a laminate formed with a base layer containing a polypropylene resin, the laminate can be heat-sealed at a low temperature by facing the sealing surfaces of the laminate and heat-sealing them together. In addition, when a packaging bag is produced using a laminate formed with a base layer containing a polypropylene resin, by heat-sealing the sealing surfaces together, the sealant film can suppress the occurrence of fusion between the sealing surfaces 30a even when a moist heat treatment is performed.
[0059] [Packaging] Next, an embodiment of the package of the present disclosure will be described with reference to Fig. 2. Fig. 2 is a cross-sectional view that illustrates a schematic diagram of one embodiment of the package of the present disclosure. As shown in Fig. 2, the packaging bag 500 includes a packaging bag 400 and a content C contained in the packaging bag 400. The packaging bag 400 is formed using a laminate 100, and the sealed surface 30a forms the inner surface of the packaging bag 400. Specifically, the packaging bag 400 is formed by overlapping two laminates 100 with their sealed surfaces 30a facing each other, and heat-sealing the peripheral portions of the sealed surfaces 30a. Thus, the packaging bag 400 includes a main body portion 401 in which the content C is contained, and a sealed portion 402 that surrounds the main body portion 401.
[0060] The packaging body 500 can suppress the occurrence of fusion between the seal surfaces 30a of the packaging bag due to the moist heat treatment. Therefore, when the packaging body 500 is opened by pulling the opposing seal surfaces 30a of the packaging bag 400 apart from each other, the packaging body 500 can be easily opened. In addition, after the packaging body 500 is opened by cutting out a part of the seal portion 402 to form an opening, the contents C can be easily taken out through the opening, and the contents C can be sufficiently discharged. As a result, the packaging bag 400 remaining after the contents C are discharged can have high recyclability. In addition, according to the packaging body 500, since the laminate 100 has low-temperature heat sealability, it is possible to suppress deterioration due to heat of layers (base layer 10 or intermediate layer 20) other than the sealant layer 30 in the laminate 100 when the packaging bag 400 is formed. Therefore, deterioration in the quality of the contents C of the packaging body 500 can be suppressed.
[0061] (Contents) The contents C are not particularly limited, but examples of the contents C include food and medicine. When the contents C are food, the packaging body 500 allows the contents C to be easily taken out after opening the packaging body 500, and allows the contents C to be sufficiently discharged. Therefore, the packaging body 500 also makes it possible to reduce food waste.
[0062] (packaging bag) In this embodiment, the packaging bag 400 includes a main body portion 401 in which the contents C are accommodated, and a seal portion 402 that surrounds the main body portion 401. That is, the packaging bag 400 is configured as a four-sided pouch. The two laminates 100 constituting the packaging bag 400 may be made of different materials and may differ from each other in thickness, shape, etc. The packaging bag 400 is not particularly limited to a four-sided pouch, and can be appropriately selected according to the application of the packaging bag. The packaging bag 400 may be, for example, a three-sided pouch, a pillow bag, a standing pouch, a gusset bag, a bag with a spout, or the like. The packaging bag 400 may be composed of three or more laminates 100. In this case, the multiple laminates 100 constituting the packaging bag 400 may be composed of different materials and may have different thicknesses, shapes, etc.
[0063] The packaging bag 400 may be used for purposes requiring heat treatment at 80° C. or higher. Examples of heat treatment include moist heat treatments such as retort treatment and boiling treatment.
[0064] [Heat-moisture treated packaging] Next, an embodiment of the moist heat treatment package of the present disclosure will be described with reference to Fig. 4. Fig. 4 is a cross-sectional view that shows a schematic diagram of one embodiment of the moist heat treatment package of the present disclosure. 4, the moist heat treatment package 700 includes a packaging bag 900 and a content C accommodated in the packaging bag 900. The packaging bag 900 is formed using a laminate 800, and a sealed surface 830a forms the inner surface of the packaging bag 900. Specifically, the packaging bag 900 is formed by overlapping two laminates 800 with their sealed surfaces 830a facing each other, heat sealing the peripheral portions of the sealed surfaces 830a, and then performing a moist heat treatment. Examples of the moist heat treatment include retort treatment and boiling treatment. Retort treatment is a pressurized and heated treatment under conditions of, for example, 0.33 MPa, 130°C, and 30 minutes, while boiling treatment is a heat treatment under conditions of, for example, 80°C, and 45 minutes. The laminate 800 includes a base layer 10 and a sealant layer 830, and a surface softening temperature of a sealing surface 830a of the sealant layer 830 by local thermal analysis is 140° C. or higher and 150° C. or lower, the sealant layer 830 contains a polypropylene-based resin, and the sealing surface 830a forms the inner surface of the packaging bag 900. The sealing surface 830a is the surface of the sealant layer 830 opposite to the base layer 10. According to this moist heat treatment package 700, the laminate 800 can suppress the occurrence of fusion between the seal surfaces 830a of the packaging bags 900 due to the moist heat treatment, so that the fusion between the seal surfaces 830a of the packaging bags 900 that have been retorted is suppressed. Therefore, the moist heat treatment package 700 can be easily opened. After opening the moist heat treatment package 700, the contents C can be easily removed and the contents C can be sufficiently discharged. As a result, the packaging bag 900 remaining after the contents C have been discharged can have high recyclability.
[0065] The surface softening temperature may be 143°C or more, 145°C or more, or 146°C or more. The surface softening temperature may also be 149°C or lower, or 148°C or lower. The surface softening temperature can be measured in the same manner as for the surface softening temperature A.
[0066] The two laminates 800 constituting the packaging bag 900 may be made of different materials and may differ from each other in thickness, shape, etc. The packaging bag 900 is not particularly limited to a four-sided pouch, and can be appropriately selected according to the application of the packaging bag. The packaging bag 900 may be, for example, a three-sided pouch, a pillow bag, a standing pouch, a gusset bag, a bag with a spout, or the like. The packaging bag 900 may be configured with three or more laminates 800. In this case, the multiple laminates 800 constituting the packaging bag 900 may be configured with different materials and may have different thicknesses, shapes, and the like. EXAMPLES
[0067] Examples of the present disclosure will be specifically described below. However, the present disclosure is not limited to the following examples.
[0068] Example 1 First, a biaxially oriented polypropylene film (OPP2) (manufactured by Futamura Chemical Co., Ltd., product name "FOR") having a thickness of 20 μm was prepared as a resin film. Next, a vapor-deposited film was formed on one surface of the resin film using a vacuum vapor deposition device, thus obtaining a gas barrier film.
[0069] Next, a polyurethane adhesive was applied to the surface of the vapor deposition layer side of the gas barrier film, and a biaxially oriented polypropylene film (OPP1) (manufactured by Futamura Chemical Co., Ltd., product name "FOR") having a thickness of 20 μm was bonded as a base layer using this adhesive. At this time, the polyurethane adhesive used was "Takelac A626 / Takenate A50" manufactured by Mitsui Chemicals, Inc.
[0070] Next, the above-mentioned polyurethane adhesive was applied to the surface of the gas barrier film opposite to the deposition layer, and a 60 μm-thick non-oriented polypropylene film (CPP film) was attached as a sealant layer via the adhesive, thus producing a laminate (base layer / deposition layer / resin film / sealant layer).
[0071] For the above sealant layer, the surface softening temperature B (before pressurization and heat treatment), surface softening temperature A (after pressurization and heat treatment), fusion strength T1 at 121°C, fusion strength T2 at 128°C, fusion strength T3 at 135°C, T2-T1, and total reflection infrared absorption spectrum of the sealing surface were calculated or measured as described below, and the surface softening temperatures B, A, fusion strengths T1, T2, T3, T2-T1, and peak intensity ratios P2 / P1, P3 / P1, and P4 / P3 were as shown in Table 1.
[0072] (Examples 2 to 9 and Comparative Examples 2 to 3) A laminate was prepared in the same manner as in Example 1, except that a CPP film having the thickness, surface softening temperatures B and A, fusion strengths T1, T2, T3, T2-T1, and peak intensity ratios P2 / P1, P3 / P1, and P4 / P3 shown in Table 1 was used as the sealant layer.
[0073] Comparative Example 1 A laminate was prepared in the same manner as in Example 1, except that a CPP film (product name "Treyfan (registered trademark) NO ZK207", manufactured by Toray Advanced Film Co., Ltd.) having the thickness, surface softening temperatures B and A, fusion strengths T1, T2, T3, T2-T1, and peak intensity ratios P2 / P1, P3 / P1, and P4 / P3 shown in Table 1 was used as the sealant layer.
[0074] (1)Surface softening temperature The surface softening temperatures B and A of the sealing surface of the sealant layer were calculated as follows.
[0075] (1-1)Surface softening temperature B First, we prepared a surface softening temperature measurement device including an atomic force microscope (AFM) MFP-3D-SA (product name) manufactured by Oxford Instruments Ltd., a local thermal analysis option Ztherm System (product name), and a cantilever AN2-200 (product name) manufactured by Anasys Instruments Ltd. with a spring constant of 0.5 to 3.5 N / m. On the other hand, a sealant film was prepared as a sealant layer to be used in the production of a laminate. Then, the surface softening temperature measurement and the shape measurement of the seal surface of the sealant film were performed using the above-mentioned surface softening temperature measurement device. The measurement mode was AC mode (tapping mode) for the shape measurement of the seal surface, and contact mode for the surface softening temperature measurement. The surface softening temperature measurement was performed in a 10 μm × 10 μm area including the center of the seal surface (intersection of the diagonal lines).
[0076] At this time, when setting the contact pressure of the cantilever (change in the deflection of the cantilever), the deflection voltage change was set to 0.2 V, the voltage application rate (heating rate) was set to 0.5 V / sec, and the maximum applied voltage was set to 5.5 V. The seal surface was heated after the detrend correction. After the seal surface expanded and the cantilever position rose, the seal surface was further heated to soften it, and the measurement was terminated when the cantilever position had dropped by 10 nm. If the vertical height of the cantilever (Z displacement) did not drop by 50 nm from the change point and reached the maximum applied voltage, the maximum applied voltage during detrend correction and measurement was increased by 0.5 V and the measurement was performed again.
[0077] The applied voltage at the point where the vertical height (Z displacement) of the cantilever was maximum was regarded as the applied voltage at the softening point, and the voltage value was read.
[0078] In order to calculate the surface softening temperature of the sealant layer, a calibration curve was created according to the measurement conditions of the sealant layer. The calibration samples used were the following four polymer materials whose melting points (melting peak temperatures) had been measured in advance using a differential scanning calorimeter (DSC), and samples were prepared in an environment below their glass transition temperatures. Polycaprolactone pellets (melting point: 60°C) Low density polyethylene pellets (melting point: 112°C) Polypropylene pellets (melting point: 166°C) ·Biaxially oriented polyethylene terephthalate film (melting point: 255℃) The measurement conditions were a voltage application rate (temperature rise rate) of 0.5 V / sec, and a maximum applied voltage of 3.5 V for polycaprolactone, 5 V for low-density polyethylene, 6 V for polypropylene, and 7.8 V for polyethylene terephthalate. When setting the cantilever contact pressure (change in cantilever deflection), the deflection voltage change was set to 0.2 V, and the seal surface was heated after detrend correction to measure the applied voltage at the softening point. The measurement position of the calibration sample was changed to measure the applied voltage at the softening point 10 times, and a calibration curve was created by approximating the average applied voltage at the softening point and the melting point (melting peak temperature) of the DSC measurement with a cubic function using the least squares method, and this calibration curve was used as the calibration curve.
[0079] Using a calibration curve of applied voltage and temperature, the temperature corresponding to the applied voltage at the softening point of the seal surface was determined, and this temperature was defined as surface softening temperature B. The results are shown in Table 1.
[0080] (1-2)Surface softening temperature A First, two sealant films each having a size of 120 mm (MD direction) x 120 mm (TD direction) were prepared from the CPP film used as the sealant layer in the examples and comparative examples. Next, the sealing surfaces of the two sealant films were placed facing each other and three sides were heat sealed to produce a packaging bag with an opening. Next, 150 mL of water was filled into the packaging bag through the opening thereof, and the opening was heat-sealed to close the opening, thereby producing a package. Next, the prepared package was heated by spraying 130°C water on it for 30 minutes under an environment of 0.33 MPa, and then cooled by spraying 40°C water on it for 10 minutes under an environment of 0.33 MPa. Finally, the sealed portion of the package was cut off, the water was drained off, and the sealed surface was dried. In this way, a sealant film that had been subjected to heat and pressure treatment was prepared. Then, for the sealant film after this heating and pressure treatment, the surface softening temperature A was calculated in the same manner as for the surface softening temperature B. The results are shown in Table 1.
[0081] (2) Fusion strength The fusion strength was measured by a T-peel test. Specifically, first, two films made of a sealant layer to be used for the measurement were prepared. The size of each film was 60 mm (MD) × 120 mm (TD). Then, the two films were overlapped, and a region 10 mm wide from the edge 600a in the TD direction was heat-sealed by heating at a predetermined heat-sealing temperature (121°C, 128°C, or 135°C) while applying a pressure of 0.05 MPa for 30 seconds, thereby forming a heat-sealed portion of 10 mm (MD) × 120 mm (TD), as shown by the diagonal lines in Figure 3. In this way, a sealed body was obtained. Next, a portion 620 indicated by a dashed line in FIG. 3 was cut out from the seal body to obtain a test piece having a size of 15 mm (TD direction)×60 mm (MD direction). Finally, a T-peel test was performed using the test piece. The T-peel test was performed in accordance with JIS K 6854-3 under the following test conditions. The tensile strength at which the heat-sealed portion of the test piece peeled off was taken as the fusion strength of the heat-sealed portion under the heat-sealing conditions. The fusion strength was measured in this manner. The results are shown in Table 1. (Test conditions) Chuck distance: 15mm -Tensile speed: 300mm / min Tensile direction: MD
[0082] (3) Peak intensity ratios P2 / P1, P3 / P1, P4 / P3 The peak intensity ratios P2 / P1, P3 / P1, and P4 / P3 were calculated as follows. First, the total reflection infrared absorption spectrum of the seal surface of the sealant layer was measured under the following measurement conditions using a total reflection infrared absorption spectrometer (product name "Spectrum Spotlight 400 / Frontier", manufactured by PerkinElmer). (Measurement conditions) Prism material: Diamond Measurement wave number range: 400~4000cm ―1 Number of times: 16 In the measured total reflection infrared absorption spectrum, 1130±5cm -1 and 680c±5cm -1 The line connecting the minimum points at was determined as the baseline. Next, in the total reflection infrared absorption spectrum, the difference between the intensity at the maximum point of the absorption peak and the intensity at the baseline was defined as the peak intensity of the absorption peak, and peak intensities P1 to P4 were calculated. Finally, the peak intensity ratios P2 / P1, P3 / P1, and P4 / P3 were calculated based on the calculated peak intensities P1 to P4. The results are shown in Table 1.
[0083] <Seal surface adhesion resistance> From the laminates produced in the examples and comparative examples, test pieces 1 and 2 were prepared under two different heating conditions as described below, and these test pieces 1 and 2 were used to judge and evaluate the sealing surface fusion resistance as described below. (1) Test piece 1 (heating conditions: 125°C, 30 min) First, two laminate pieces each having a length of 120 mm in the MD and TD directions were cut out from the laminates produced in the examples and comparative examples. Next, the two cut-out pieces of the laminate were overlapped with their sealed surfaces facing each other, and with the sealed surfaces in close contact with each other, the four sides of the laminate piece were heat sealed with an impulse sealer to produce a fused body. The fused specimen was heated by spraying hot water at 125°C for 30 minutes under pressure of 0.21 MPa, and then cooled by spraying water at 40°C for 10 minutes under pressure of 0.21 MPa, after which the fused specimen was left to stand at room temperature for one day. After standing, the heat-sealed portions on the four sides of the fused specimen were cut out, and the remaining central portion of the fused specimen was prepared as test piece 1.
[0084] (2) Test piece 2 (heating conditions: 130℃, 30min) Test piece 2 was prepared under the same heating conditions as heating condition 1, except that the fused body was heated by spraying hot water at 130° C. for 30 minutes.
[0085] (3) Judgment and evaluation of sealing surface adhesion resistance For the test pieces 1 and 2 prepared as described above, the two laminate pieces were each pinched by hand and pulled apart, and judged according to the resistance felt when peeling, using the following five-level judging criteria. The results are shown in Table 1. (Judgment criteria) 1: No resistance at all when peeling off 2: Almost no resistance when peeling off 3: There is a slight resistance when peeling off 4: There is a strong resistance when peeling off 5: The test piece is fused and there is a significant resistance (when peeled off, deformation or changes in the appearance of the sealing surface (such as cohesive peeling) occur) The test pieces judged as "1" and "2" were rated as "◎", the test pieces judged as "3" were rated as "◯", the test pieces judged as "4" were rated as "△", and the test pieces judged as "5" were rated as "X". The results are shown in Table 1.
[0086] <Low temperature heat sealability> The low-temperature heat sealability was evaluated based on the seal initiation temperature of the sealant layer used in the examples and comparative examples. The seal initiation temperature of the sealant layer was measured as follows. First, as shown in Figure 3, two sealant layers measuring 120 mm (TD) x 60 mm (MD) were prepared, and these two sealant layers were heated at T°C while being pressurized at 0.2 MPa for 1 second with a seal width of 10 mm to prepare a heat-sealed body. At this time, the heat-sealed bodies were prepared by setting T to a heating temperature between 130°C and 170°C, which differed by 2°C each. Then, test pieces measuring 60 mm (TD) x 15 mm (MD) were prepared from these heat-sealed bodies. A T-peel test was performed on each of the test pieces prepared as described above. The T-peel test was performed in accordance with JIS K 6854-3. Specifically, the T-peel test was performed in the MD direction under the conditions of a chuck distance of 15 mm and a tensile speed of 300 mm / min. The lowest temperature at which the peel strength was 10 N / 15 mm or more was determined as the sealing start temperature of the sealant layer.
[0087] The low-temperature heat sealability of the sealant layer was evaluated based on the following criteria, and the results are shown in Table 1. (Evaluation Criteria) ○: Sealing start temperature is less than 155℃ ×: Sealing start temperature is 155℃ or higher
[0088] [Table 1]
[0089] From the results shown in Table 1, in Examples 1 to 9, the sealing start temperature was less than 155°C, and the sealing surface adhesion resistance was judged to be 1 to 4 under each of the heating conditions of "125°C, 30 min" and "130°C, 30 min", confirming that the laminate had low-temperature heat sealability but did not fuse between the sealing surfaces. In contrast, in Comparative Example 1, the sealing start temperature was 156°C, which was 155°C or higher. Moreover, in Comparative Examples 2 and 3, the sealing surface adhesion resistance was judged to be 5 under each of the heating conditions of "125°C, 30 min" and "130°C, 30 min", confirming that the sealing surfaces did fuse together.
[0090] From the above, it was confirmed that the laminate of the present disclosure has low-temperature heat sealability and also has excellent resistance to sealing surface fusion even when subjected to moist heat treatment.
[0091] The outline of this disclosure is as follows. [1] A laminate comprising at least a base layer and a sealant layer, the seal surface of the sealant layer having a surface softening temperature of 110°C or higher and 140°C or lower as determined by local thermal analysis, the sealant layer having a fusion strength of 2.0 N / 15 mm or lower when heat sealed to the same sealant layer under conditions of 121°C, 0.05 MPa, and 30 seconds, and the base layer and the sealant layer containing a polypropylene-based resin. [2] The laminate according to [1], wherein the surface softening temperature of the sealing surface determined by local thermal analysis after the laminate is subjected to a pressure and heat treatment under conditions of 0.33 MPa, 130°C, and 30 minutes is 140°C or higher and 150°C or lower. [3] The laminate according to [1] or [2], wherein when the sealant layer is heat-sealed to the same sealant layer as the sealant layer under conditions of 0.05 MPa and 30 seconds, T2-T1 is 10.0 N / 15 mm or less, where T1 is the fusion strength when the heat sealing temperature is 121°C (N / 15 mm) and T2 is the fusion strength when the heat sealing temperature is 128°C (N / 15 mm). [4] In the total reflection infrared absorption spectrum of the sealing surface, -1 More than 983cm -1 The peak intensity of the absorption peak appearing in the first region below is P1, 700 cm -1 More than 750cm -1 The laminate according to any one of [1] to [3], wherein, when the peak intensity of one absorption peak appearing in the following second region is P2, and when two or more absorption peaks are present in the second region, the peak intensity of the absorption peak on the higher wavenumber side of the two absorption peaks having the largest peak intensities in the second region is P3, and the peak intensity of the absorption peak on the lower wavenumber side is P4, the peak intensity ratio P2 / P1 or P3 / P1 is 0.15 or less, or P4 / P3 is 1.5 or less. [5] The laminate according to any one of [1] to [4], wherein the sealant layer has a fusion strength of 10.0 N / 15 mm or less when heat-sealed to the same sealant layer under conditions of 135°C, 0.05 MPa and 30 seconds. [6] The laminate according to any one of [1] to [5], further comprising a gas barrier layer. [7] A packaging bag obtained by using the laminate according to any one of [1] to [6] above and heat-sealing the sealing surfaces together. [8] The packaging bag described in [7], which is used for applications requiring heat treatment at 80°C or higher. [9] A sealant film containing a polypropylene-based resin, wherein when the surface of the sealant film is used as a sealing surface, the surface softening temperature of the sealing surface by local thermal analysis is 110°C or higher and 140°C or lower, and when the sealant film is heat sealed to the same sealant film under conditions of 121°C, 0.05 MPa, and 30 seconds, the sealant film has a fusion strength of 2.0 N / 15 mm or less.
[10] A packaging body comprising a packaging bag and contents contained in the packaging bag, the packaging bag being formed using a laminate described in any one of [1] to [6], and the sealing surface forming an inner surface of the packaging bag.
[11] A moist heat treated package comprising a packaging bag and contents contained within the packaging bag, the packaging bag being formed using a laminate, the laminate comprising at least a base material layer and a sealant layer, the surface softening temperature of the sealing surface of the sealant layer being 140°C or higher and 150°C or lower as determined by local thermal analysis, the base material layer and the sealant layer containing a polypropylene-based resin, and the sealing surface constituting the inner surface of the packaging bag. [Explanation of symbols]
[0092] 10...base material layer, 20...intermediate layer, 30,830...sealant layer, 30a,830a...seal surface, 100,800...laminate, 400,900...packaging bag, 500...packaging body, 600...sealed body, 610...heat-sealed portion, 700...moisture-heat-treated packaging body, C...contents
Claims
1. The adhesive tape comprises at least a base layer and a sealant layer, and the surface softening temperature of the sealant layer measured by local thermal analysis is 110° C. or more and 140° C. or less; the sealant layer has a fusion strength of 2.0 N / 15 mm or less when heat-sealed to the same sealant layer under conditions of 121° C., 0.05 MPa, and 30 seconds; The laminate, wherein the base layer and the sealant layer contain a polypropylene-based resin.
2. The laminate according to claim 1, wherein the surface softening temperature of the sealing surface determined by local thermal analysis after the laminate is subjected to a pressure and heat treatment under conditions of 0.33 MPa, 130°C, and 30 minutes is 140°C or higher and 150°C or lower.
3. When the sealant layer is heat-sealed to the same sealant layer as the sealant layer under conditions of 0.05 MPa and 30 seconds, the fusion strength when the heat sealing temperature is 121° C. is T1 (N / 15 mm) and the fusion strength when the heat sealing temperature is 128° C. is T2 (N / 15 mm), The laminate according to claim 1 or 2, wherein T2-T1 is 10.0 N / 15 mm or less.
4. In the total reflection infrared absorption spectrum of the sealing surface, -1 983cm or more -1 The peak intensity of the absorption peak appearing in the first region below is P1, 700 cm -1 More than 750cm -1 When the peak intensity of one absorption peak appearing in the following second region is P2, and when two or more absorption peaks are present in the second region, the peak intensity of the absorption peak on the higher wavenumber side of the two absorption peaks having the largest peak intensities in the second region is P3, and the peak intensity of the absorption peak on the lower wavenumber side is P4, 3. The laminate according to claim 1, wherein the peak intensity ratio P2 / P1 or P3 / P1 is 0.15 or less, or the peak intensity ratio P4 / P3 is 1.5 or less.
5. 3. The laminate according to claim 1, wherein the sealant layer has a fusion strength of 10.0 N / 15 mm or less when heat-sealed to the same sealant layer under conditions of 135°C, 0.05 MPa and 30 seconds.
6. The laminate according to claim 1 or 2, further comprising a gas barrier layer.
7. A packaging bag obtained by using the laminate according to claim 1 or 2 and heat sealing the sealing surfaces together.
8. The packaging bag according to claim 7, which is used for applications in which a heat treatment of 80°C or more is performed.
9. A sealant film containing a polypropylene-based resin, The surface softening temperature of the sealant film according to local thermal analysis is 110° C. or more and 140° C. or less; The sealant film has a fusion strength of 2.0 N / 15 mm or less when heat-sealed to the same sealant film under conditions of 121° C., 0.05 MPa and 30 seconds.
10. A packaging bag and a content contained in the packaging bag, The packaging bag is formed using the laminate according to claim 1 or 2, A package, wherein the sealing surface constitutes the inner surface of the packaging bag.
11. A packaging bag and a content contained in the packaging bag, The packaging bag is formed using a laminate, The laminate comprises: The adhesive tape has at least a base layer and a sealant layer, and the surface softening temperature of the sealant layer measured by local thermal analysis is 140° C. or higher and 150° C. or lower; the base layer and the sealant layer contain a polypropylene-based resin, The sealing surface constitutes the inner surface of the packaging bag.
Citation Information
Patent Citations
Ultralow temperature heat-sealing tape-casting polypropylene aluminum plating film
CN103802389A
Polypropylene composite film
JP1996238733A
Polypropylene resin composition and non-stretched film
JP1999293062A
Polypropylene biaxially stretched double-layer film
JP2005305767A
Polyolefin based laminated film for packaging
JP2006116891A